Psychological and Pedagogical Foundations of Forming Environmental Culture among Students by Means of Tourist Activities - BODNEVA, Natalya; SRIBNAYA, Tatiana; FURSOVA, Dilara; STAROSTENKOV, Nikolai; ESAULOVA, Kira (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019, 2019)
Regardless of the development of human society and the introduction of new technologies (information, information-telecommunication), a person is mainly a biosocial being. Besides significant social characteristics and virtues, the main feature of each person is belonging to a large self-sufficient system. Thus, human beings differ from other species since they can exist in nature while creating their own culture and living conditions by means of mental and physical work. With the course of time and the emergence of innovations, the environment where people live undergoes global changes. The speed and extent of technological impact on the environment cannot be assessed due to many factors, including the multiplicative negative effect on the environment caused by products of modern civilization. In this regard, such science as ecology has become especially relevant. Environmental knowledge is vital to make the dream of many generations of thinkers come true and create a decent human environment ensuring the harmony of people and nature. Ecology helps analyze the impact of human life on the environment. The study of ecology cannot be conducted only at the level of the scientific community; each person should know its elementary problems and ways to build their personal life to effectively promote the harmonious development of society. Therefore, this article addresses the problem of environmental education, including the use of modern achievements, such as information, information and telecommunication technologies. The formation of environmental consciousness is necessary so that global problems are not regarded as mythical threats.